Brida : [compact disc, unabridged] : a novel - Coelho, Paulo (HarperCollins Audio, 2008)
Young Brida sets off on a journey in search of magical knowledge. Her travels soon bring her to a group of people all too willing to share their teachings of all things spiritual. As she learns, Brida will come to a choice between the people around her and her thirst for wisdom.